1988
DOI: 10.4141/cjps88-145
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration of Dormant Apple Buds at Different Stages of Cold Acclimation to Induce Cryopreservability in Different Cultivars

Abstract: . 1988. Dehydration of dormant apple buds at different stages of cold acclimation to induce cryopreservability in different cultivars. Can. J. Plant Sci. 68: 1169-1176. Survival in liquid nitrogen of dormant vegetative buds from several cold-hardened apple cultivars was greater with buds which were dehydrated prior to cryopreservation than with nondehydrated buds. Buds collected early in the cold-acclimating period suffered injury as a result of dehydration, but the percent survival of the dehydrated bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 7 publications
(4 reference statements)
0
25
0
Order By: Relevance
“…This is reasonable since MC [ 30 % would negatively impact survival. Tyler and Stushnoff (1988b) investigated the effect of dehydration depending on the physiological stage of the material. When cold acclimated buds were processed during winter time, all apple cultivars became resistant to moderate dehydration stress.…”
Section: Discussionmentioning
confidence: 99%
“…This is reasonable since MC [ 30 % would negatively impact survival. Tyler and Stushnoff (1988b) investigated the effect of dehydration depending on the physiological stage of the material. When cold acclimated buds were processed during winter time, all apple cultivars became resistant to moderate dehydration stress.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the water in the primordial shoot freezes out through the crown (medullary bridge) and consequently it is the crown that plays the major role in freezing avoidance in the primordial shoots of conifer buds [12,13]. Tyler & Stusnoff [18] used dormant vegetative apple buds in their cryoexperiments, dehydrating them by keeping them at -4°C for various lengths of time and then cooling them slowly to -30°C. The samples were kept at -30°C for one hour before immersion in liquid nitrogen.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of the frozen buds decreased markedly (down to 7-27%) towards to the end of April. The degree of success varies with the physiological state of the buds [18] and the amount of water (Table 2). For these reasons, freeze preservation of vegetative buds cannot be done in May.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryopreservation of temperate woody species was started in Japan when Sakai (1960) demonstrated that winter hardy twigs of poplar and willow survived slow cooling and then immersion in liquid nitrogen. Since then this method has been applied and developed further for preservation of dormant buds of fruit species (Sakai and Nishiyama 1978, Tyler and Stushnoff 1988, Towill et al 2004, Toldam-Andersen et al 2007, Towill and Ellis 2008. In Finland, studies have been carried out to develop cryopreservation techniques for forest tree breeding materials since 1990's and the method for cryopreservation of dormant buds together with recovery through in vitro culture has been introduced.…”
Section: Introductionmentioning
confidence: 99%